Thermoplastic resin composition, extrusion molded product, and foam molded product

The thermoplastic resin composition with specific polymer and carbon filler distribution addresses flexibility and moldability issues in thermally conductive foam sheets, achieving high thermal conductivity and flexibility in molded articles.

JP7618431B2Active Publication Date: 2025-01-21ENEOS MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020202495
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-07
Publication Date
2025-01-21
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

Conventional thermally conductive foam sheets used in electronic devices suffer from reduced flexibility due to high filler content, leading to impaired moldability and frequent interfacial peeling during molding, which affects the appearance of the molded product.

Method used

A thermoplastic resin composition comprising a polymer with a durometer hardness of 90A or less and a melting point of 23°C or higher, a polypropylene thermoplastic resin with a melt tension of 3.0 cN or more at 210°C, and carbon filler, which forms a continuous phase with the filler unevenly distributed, enhancing thermal conductivity and flexibility.

Benefits of technology

The composition produces molded articles with excellent moldability, thermal conductivity, and flexibility, reducing interfacial peeling and improving processability while maintaining mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618431000003
    Figure 0007618431000003
  • Figure 0007618431000004
    Figure 0007618431000004
  • Figure 0007618431000005
    Figure 0007618431000005
Patent Text Reader

Abstract

To provide a thermoplastic resin composition capable of producing a molded body having good molding processability and excellent thermal conductivity and flexibility.SOLUTION: There is provided a thermoplastic resin composition which comprises (A) a polymer having a durometer hardness of 90A or less and a melting point of 23°C or more, (B) a polypropylene-based thermoplastic resin having a melt tension at 210°C at a take-off speed of 2.0 m / m of 3.0 cN or more and (C) a carbon-based filler, wherein the polymer (A) has a melting point derived from an ethylene crystal structure of 23°C or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition, and to an extrusion molded article and a foam molded article produced using the composition. [Background technology]

[0002] The increase in heat generated by components and devices due to the high performance and integration of components in electronic devices and the miniaturization of the devices is becoming more and more significant. If no heat countermeasures are taken, not only will the functions and performance of the components be reduced and their lifespans be shortened, but the devices themselves may become hot and cause low-temperature burns or fires. As a heat countermeasure for these components, a heat path is generally created by contacting the heat-generating components mounted inside the devices with metal components that also serve as heat sinks, such as sheet metal and shielding materials inside the devices, using a heat dissipation material to reduce the temperature of the heat-generating components. A silicone resin foam sheet containing a heat-conductive filler is an example of a conventional heat dissipation material. A heat-conductive foam sheet for electronic devices containing an elastomer resin and a heat conductor such as magnesium oxide or aluminum oxide is also known (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2014 / 083890 Summary of the Invention [Problem to be solved by the invention]

[0004] Thermally conductive foam sheets used inside electronic devices require flexibility in addition to thermal conductivity in terms of conformability to uneven surfaces. However, conventional thermally conductive foam sheets tend to lose flexibility because they contain a relatively large amount of thermally conductive filler to improve heat dissipation. In addition, when the filler is highly filled, the interaction between the filler and the resin at the interface is weak, so that interfacial peeling occurs frequently during molding, and the appearance of the molded sheet tends to be impaired.

[0005] Some aspects of the present invention provide a thermoplastic resin composition that has good moldability and can produce a molded article having excellent thermal conductivity and flexibility. Some aspects of the present invention also provide an extrusion molded article produced using the composition. Some aspects of the present invention also provide a foam molded article produced using the composition. [Means for solving the problem]

[0006] One embodiment of the thermoplastic resin composition according to the present invention is (A) a polymer having a durometer hardness of 90A or less and a melting point of 23°C or more; (B) a polypropylene-based thermoplastic resin having a melt tension of 3.0 cN or more at 210°C and a take-up speed of 2.0 m / min; and (C) Carbon-based filler A thermoplastic resin composition comprising: The polymer (A) is characterized in that it has a melting point of 23° C. or higher, which is derived from an ethylene crystal structure.

[0007] In one embodiment of the thermoplastic resin composition, The (A) polymer may have a melting enthalpy of 5 to 150 J / g as measured by a differential scanning calorimeter under the following conditions. conditions: (1) Cool from 200°C to -150°C at 10°C / min (2) Hold at -150℃ for 1 minute (3) Heat from -150°C to 200°C at 20°C / min.

[0008] In any one of the embodiments of the thermoplastic resin composition, The polymer (A) may contain one or more polymers selected from hydrogenated diene polymers and ethylene / α-olefin polymers.

[0009] In any one of the embodiments of the thermoplastic resin composition, The hydrogenated diene polymer is A hydrogenated diene triblock copolymer obtained by hydrogenating a conjugated diene triblock copolymer having blocks A at both ends and block B in the middle, the 1,2-vinyl group content of said block A is less than 25 mol % and the 1,2-vinyl group content of said block B is 25 mol % or more; When the entire conjugated diene triblock copolymer is taken as 100% by mass, the block A is 5 to 90% by mass and the block B is 10 to 95% by mass, 80% or more of the double bonds derived from the conjugated diene monomer units contained in the conjugated diene triblock copolymer are hydrogenated, The number average molecular weight after hydrogenation may be 50,000 to 700,000.

[0010] In any one of the embodiments of the thermoplastic resin composition, The primary structure of the (C) carbon-based filler is any one of a spherical, plate-like, or fibrous shape, The average particle size in the case of a sphere, the average thickness in the case of a plate, and the average diameter in the case of a fiber may be 1 μm or less.

[0011] In any one of the embodiments of the thermoplastic resin composition, The volume fraction of the (C) carbon-based filler in the thermoplastic resin composition may be 15 to 40 volume %.

[0012] In any one of the embodiments of the thermoplastic resin composition, the (A) polymer and the (B) thermoplastic resin form a continuous phase containing the (A) polymer and a continuous or discontinuous phase containing the (B) thermoplastic resin; More than 50% by mass of the (C) carbon-based filler may be present in the (A) polymer-containing continuous phase.

[0013] In any one of the embodiments of the thermoplastic resin composition, The continuous phase containing the polymer (A) may have a thickness of 5 μm or less.

[0014] One embodiment of the extrusion molded body according to the present invention is The thermoplastic resin composition according to any one of the above embodiments is used to produce the product.

[0015] One embodiment of the foamed molded article according to the present invention is The thermoplastic resin composition according to any one of the above embodiments is used to produce the product. Effect of the Invention

[0016] The thermoplastic resin composition according to the present invention has good moldability and can produce a molded article having excellent thermal conductivity and flexibility. In addition, by using the thermoplastic resin composition according to the present invention, a foamed molded article or an extrusion molded article having excellent thermal conductivity and flexibility can be produced. [Brief description of the drawings]

[0017] [Figure 1] 1 is a TEM photograph showing a continuous phase structure containing an ethylene-α-olefin copolymer (X) of the thermoplastic resin composition produced in Example 8. [Diagram 2] FIG. 2 is an enlarged TEM photograph of a portion of FIG. [Diagram 3] 1 is a TEM photograph showing a continuous phase structure containing an ethylene-α-olefin copolymer (X) of the thermoplastic resin composition produced in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the embodiments described below, and should be understood to include various modified examples that are implemented within the scope of the present invention.

[0019] In this specification, a numerical range described using "X to Y" is interpreted as including the numerical value X as the lower limit and including the numerical value Y as the upper limit.

[0020] In this specification, (A) a polymer having a durometer hardness of 90A or less and a melting point of 23°C or higher is sometimes abbreviated as "component (A)", (B) a polypropylene-based thermoplastic resin having a melt tension of 3.0 cN or more at 210°C and a take-up speed of 2.0 m / min is sometimes abbreviated as "component (B)", and (C) a carbon-based filler is sometimes abbreviated as "component (C)".

[0021] 1.Thermoplastic resin composition The thermoplastic resin composition according to one embodiment of the present invention comprises: (A) a polymer having a durometer hardness of 90A or less and a melting point of 23°C or more; (B) a polypropylene-based thermoplastic resin having a melt tension of 3.0 cN or more at 210°C and a take-up speed of 2.0 m / min; and (C) Carbon-based filler A thermoplastic resin composition comprising: The polymer (A) is characterized in that it has a melting point of 23° C. or higher, which is derived from an ethylene crystal structure. Hereinafter, each component contained in the thermoplastic resin composition according to this embodiment will be described.

[0022] 1.1.(A) Component The thermoplastic resin composition according to the present embodiment contains (A) a polymer having a durometer hardness of 90A or less, and a melting point and a melting point derived from an ethylene crystal structure of 23°C or more.

[0023] The durometer hardness of component (A) is 90A or less, preferably 85A or less, more preferably 80A or less, and particularly preferably 75A or less. When the durometer hardness of component (A) is within the above range, it is not too hard, so that the molding processability is good, and a molded product with excellent flexibility can be produced. The durometer hardness can be measured using a type A durometer conforming to JIS K 6253.

[0024] The (A) component has a melting point and a melting point derived from the ethylene crystal structure of 23° C. or higher. When the (A) component melting point and the melting point derived from the ethylene crystal structure are both 23° C. or higher, the stretch crystallinity is improved, and a molded article having an excellent balance between flexibility and mechanical strength can be produced. The (A) component melting point and the melting point derived from the ethylene crystal structure are preferably 30° C. or higher, more preferably 35° C. or higher, and even more preferably 40° C. or higher. It is particularly preferably 50° C. or higher. The upper limits of the melting point of component (A) and the melting point derived from the ethylene crystal structure are preferably 200° C. or lower, more preferably 180° C. or lower, and particularly preferably 160° C. or lower. The melting point of component (A) and the melting point derived from the ethylene crystal structure are values ​​indicated as temperatures at which the amount of heat absorbed due to crystalline melting shows a peak in a melting curve obtained using a differential scanning calorimeter (DSC).

[0025] Furthermore, the component (A) preferably has a melting enthalpy measured by a differential scanning calorimeter (DSC) under the following conditions (1) to (3) of 5 to 150 J / g, more preferably 10 to 130 J / g, and particularly preferably 15 to 100 J / g. conditions: (1) Cool from 200°C to -150°C at 10°C / min (2) Hold at -150℃ for 1 minute (3) Heat from -150°C to 200°C at 20°C / min. When the melting enthalpy of component (A) is within the above range, the stretching crystallinity is improved, and thus a molded product having an excellent balance between flexibility and mechanical strength may be produced. In this specification, the melting enthalpy is a value shown as the sum of the endothermic heat amounts caused by crystal melting in the process of increasing the temperature from -150°C to 200°C in the melting curve obtained by using DSC under the above conditions.

[0026] Component (A) is not particularly limited as long as it has a durometer hardness of 90A or less and a melting point and a melting point derived from an ethylene crystal structure of 23°C or more, but it preferably contains one or more polymers selected from hydrogenated diene polymers obtained by hydrogenating (also simply referred to as "hydrogenation" in this specification) diene polymers having structural units derived from a conjugated diene compound, and ethylene-α-olefin polymers having structural units derived from ethylene and structural units derived from an α-olefin. Hydrogenated diene polymers and ethylene-α-olefin polymers are described in detail below.

[0027] 1.1.1. Hydrogenated diene polymers The hydrogenated diene polymer is not particularly limited, but is preferably a hydrogenated diene triblock copolymer obtained by hydrogenating a conjugated diene triblock copolymer having block A with a 1,2-vinyl group content of less than 25 mol% at both ends and block B with a 1,2-vinyl group content of 25 mol% or more in the middle. The 1,2-vinyl group content can be calculated by the Morello method using infrared absorption spectroscopy. The 1,2-vinyl group content of the hydrogenated product means the vinyl group content of the corresponding polymer before hydrogenation.

[0028] Block A is preferably a polymer block mainly composed of 1,3-butadiene. "Mainly composed of 1,3-butadiene" means that 90% by mass or more, preferably 95% by mass or more of all the constituent units of block A are constituent units derived from 1,3-butadiene.

[0029] In order to suppress a drop in the melting point of the crystals after hydrogenation, the 1,2-vinyl group content of block A is preferably 20 mol % or less, and more preferably 15 mol % or less.

[0030] Block B is preferably a conjugated diene polymer block having a structural unit derived from a conjugated diene compound. Examples of the conjugated diene compound include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, and chloroprene. Among these, 1,3-butadiene, isoprene, and 1,3-pentadiene are preferred, and 1,3-butadiene is more preferred. It is more preferable that the block B is composed of two or more kinds of monomer units.

[0031] From the viewpoint of improving the flexibility of the molded product, the 1,2-vinyl group content of block B is preferably from 25 mol % to 95 mol %, and more preferably from 25 mol % to 85 mol %.

[0032] When block B is a conjugated diene polymer block, block B may contain a structural unit derived from an aromatic vinyl compound. When block B contains a structural unit derived from an aromatic vinyl compound, the content of the structural unit derived from an aromatic vinyl compound is preferably 35% by mass or less, more preferably 30% by mass or less, and particularly preferably 25% by mass or less, from the viewpoint of maintaining the flexibility of the molded product, when the total structural units of block B are taken as 100% by mass.

[0033] Examples of aromatic vinyl compounds that can be a constituent unit of block B include styrene, tert-butylstyrene, α-methylstyrene, p-methylstyrene, p-ethylstyrene, divinylbenzene, 1,1-diphenylstyrene, vinylnaphthalene, vinylanthracene, N,N-diethyl-p-aminoethylstyrene, vinylpyridine, etc. Among these, styrene is preferred.

[0034] When the entire conjugated diene triblock copolymer before hydrogenation is taken as 100% by mass, the content of block A is preferably 5 to 90% by mass, and more preferably 10 to 80% by mass. On the other hand, when the entire conjugated diene triblock copolymer before hydrogenation is taken as 100% by mass, the content of block B is preferably 10 to 95% by mass, and more preferably 20 to 90% by mass.

[0035] The conjugated diene triblock copolymer before hydrogenation can be obtained by living anionic polymerization of a conjugated diene compound, or a conjugated diene compound and an aromatic vinyl compound, using an organic alkali metal compound as a polymerization initiator in an inert organic solvent, such as an aliphatic hydrocarbon solvent, such as pentane, hexane, heptane, or octane; an alicyclic hydrocarbon solvent, such as cyclopentane, methylcyclopentane, cyclohexane, or methylcyclohexane; or an aromatic hydrocarbon solvent, such as benzene, xylene, toluene, or ethylbenzene. Note that a hydrogenated diene block copolymer can be easily obtained by hydrogenating the obtained conjugated diene triblock copolymer.

[0036] The organic alkali metal compound used as the polymerization initiator includes an organic lithium compound, an organic sodium compound, etc. Among these, an organic lithium compound such as n-butyl lithium, sec-butyl lithium, tert-butyl lithium, etc. is preferable. The amount of the organic alkali metal compound used is not particularly limited, but is usually 0.02 to 15 parts by mass, preferably 0.03 to 5 parts by mass, based on 100 parts by mass of the monomer.

[0037] The polymerization temperature is usually -10 to 150°C, preferably 0 to 120°C. The atmosphere of the polymerization system is preferably replaced with an inert gas such as nitrogen gas. The polymerization pressure is not particularly limited as long as it is within a pressure range sufficient to maintain the monomer and the solvent in a liquid phase. The method of feeding the monomer into the polymerization system is not particularly limited, and examples thereof include a method of feeding the monomer all at once, continuously, intermittently, or a combination thereof.

[0038] The hydrogenated diene triblock copolymer can be obtained by partially or selectively hydrogenating the conjugated diene triblock copolymer obtained as described above before hydrogenation. There are no particular limitations on the hydrogenation method or reaction conditions. The hydrogenation is usually carried out at 20 to 150° C., 0.1 The reaction is carried out under hydrogen pressure of up to 10 MPa in the presence of a hydrogenation catalyst.

[0039] The hydrogenation rate can be arbitrarily selected by changing the amount of hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, or the reaction time. As the hydrogenation catalyst, a compound containing any of the metals of Groups Ib, IVb, Vb, VIb, VIIb, and VIII of the periodic table of elements, for example, a compound containing Ti, V, Co, Ni, Zr, Ru, Rh, Pd, Hf, Re, or Pt atoms, can be used. Specifically, for example, metallocene compounds such as Ti, Zr, Hf, Co, Ni, Pd, Pt, Ru, Rh, and Re; supported heterogeneous catalysts in which metals such as Pd, Ni, Pt, Rh, and Ru are supported on a support such as carbon, silica, alumina, and diatomaceous earth; homogeneous Ziegler-type catalysts in which an organic salt or acetylacetone salt of a metal element such as Ni or Co is combined with a reducing agent such as organoaluminum; organometallic compounds or complexes such as Ru and Rh; and fullerenes and carbon nanotubes in which hydrogen is absorbed can be mentioned. Among these, metallocene compounds containing any of Ti, Zr, Hf, Co, and Ni are preferred because they can undergo hydrogenation in an inert organic solvent in a homogeneous system. Furthermore, metallocene compounds containing any of Ti, Zr, and Hf are preferred. In particular, hydrogenation catalysts obtained by reacting titanocene compounds with alkyl lithium are preferred because they are inexpensive and particularly useful industrially. The hydrogenation catalysts may be used alone or in combination of two or more.

[0040] After hydrogenation, if necessary, the catalyst residue is removed or a phenol-based or amine-based antioxidant is added, and then the hydrogenated diene triblock copolymer is isolated. The hydrogenated diene triblock copolymer can be isolated, for example, by a method of adding acetone or alcohol to a hydrogenated diene triblock copolymer solution to cause precipitation, or by a method of pouring a hydrogenated diene triblock copolymer solution into hot water under stirring and distilling off the solvent.

[0041] The hydrogenation rate of the hydrogenated diene triblock copolymer is preferably 80% or more, more preferably 90% or more, and particularly preferably 95 to 100%. When the hydrogenation rate is 80% or more, the thermal stability and durability tend to be improved.

[0042] The lower limit of the number average molecular weight (Mn) of the hydrogenated diene triblock copolymer after hydrogenation is preferably 50,000, more preferably 80,000, and particularly preferably 100,000. The upper limit of the number average molecular weight (Mn) of the hydrogenated diene block copolymer after hydrogenation is preferably 700,000, more preferably 650,000, and particularly preferably 600,000. When the number average molecular weight (Mn) of the hydrogenated diene triblock copolymer after hydrogenation is within the above range, a molded product having an excellent balance between mechanical properties and flexibility is easily obtained, and molding processability tends to be good.

[0043] 1.1.2. Ethylene-α-olefin polymers The ethylene-α-olefin polymer may contain structural units derived from monomers other than ethylene and α-olefin. The ethylene-α-olefin polymer may be any of a random copolymer, an alternating copolymer, and a block copolymer, but is preferably a random copolymer or a block copolymer.

[0044] The α-olefin is preferably an α-olefin having 3 to 10 carbon atoms, more preferably an α-olefin having 3 to 8 carbon atoms. Specific examples of the α-olefin include propylene, 1-butene, 2-methylpropene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. In synthesizing the ethylene-α-olefin polymer, these α-olefins may be used alone or in combination of two or more.

[0045] Monomers other than ethylene and α-olefins include 1,3-butadiene, 2-methyl Examples of the compound include conjugated diene compounds having 4 to 8 carbon atoms, such as 1,3-butadiene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene; non-conjugated diene compounds having 5 to 15 carbon atoms, such as dicyclopentadiene, 5-ethylidene-2-norbornene, 1,4-hexadiene, 1,5-dicyclooctadiene, 7-methyl-1,6-octadiene, and 5-vinyl-2-norbornene; vinyl carboxylate esters, such as vinyl acetate; unsaturated carboxylate esters, such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate; and unsaturated carboxylic acids, such as acrylic acid and methacrylic acid. Among these, non-conjugated dienes having 5 to 15 carbon atoms are preferred, and 5-ethylidene-2-norbornene and dicyclopentadiene are more preferred. In synthesizing the ethylene-α-olefin polymer, these monomers other than ethylene and α-olefin may be used alone or in combination of two or more.

[0046] When the total mass of the ethylene-α-olefin polymer is taken as 100% by mass, the content of structural units derived from ethylene is preferably 40 to 85% by mass, more preferably 50 to 80% by mass, and particularly preferably 55 to 70% by mass.

[0047] When the total mass of the ethylene-α-olefin polymer is taken as 100% by mass, the content of structural units derived from α-olefin is preferably 10 to 50% by mass, more preferably 15 to 45% by mass, and particularly preferably 25 to 40% by mass.

[0048] When the total mass of the ethylene-α-olefin polymer is taken as 100% by mass, the content of structural units derived from monomers other than ethylene and α-olefin is preferably 0 to 15% by mass, more preferably 0 to 8% by mass, and particularly preferably 0 to 5% by mass.

[0049] The content ratio of the structural units derived from each monomer in the ethylene-α-olefin polymer can be determined by infrared spectroscopy. Specifically, the infrared absorption spectrum of the ethylene-α-olefin polymer is measured using an infrared spectrophotometer, and the content ratio of the structural units derived from each monomer in the ethylene-α-olefin polymer can be calculated according to the method described in "Characterization of Polyethylene by Infrared Absorption Spectroscopy (Takayama, Usami, et al.)" or "Die Makromolekulare Chemie, 177, 461 (1976) (McRae, MA, Madam S, WF, et al.)".

[0050] Specific examples of ethylene-α-olefin polymers include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, ethylene-(ethylene-1-octene) copolymers, ethylene-propylene-1-butene copolymers, ethylene-propylene-1-hexene copolymers, ethylene-propylene-1-octene copolymers, ethylene-propylene-5-ethylidene-2-norbornene copolymers, ethylene-propylene-dicyclopentadiene copolymers, ethylene-propylene-1,4-hexadiene copolymers, and ethylene-propylene-5-vinyl-2-norbornene copolymers. Among these, ethylene-1-octene copolymers and ethylene-(ethylene-1-octene) copolymers are preferred. These ethylene-α-olefin polymers may be used alone or in combination of two or more.

[0051] Examples of the production of ethylene-α-olefin polymers include a method of copolymerizing ethylene, an α-olefin, and a monomer other than ethylene and an α-olefin in the presence of a known complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, a nonmetallocene complex, etc. Polymerization methods include a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, etc.

[0052] 1.2.(B) Component The thermoplastic resin composition according to the present embodiment contains (B) a polypropylene-based thermoplastic resin having a melt tension of 3.0 cN or more at 210°C and a take-up speed of 2.0 m / min. The melt tension of the (B) component at 210°C and a take-up speed of 2.0 m / min is 3.0 cN or more, preferably 5.0 cN or more, and more preferably 8.0 cN or more. When the melt tension is 3.0 cN or more, the melt tension of the thermoplastic resin composition according to the present embodiment can be increased, so that the moldability tends to be improved. In addition, a molded product having an excellent balance between mechanical strength and flexibility can be produced.

[0053] In this specification, the "melt tension" refers to the tension generated when a polypropylene-based thermoplastic resin heated and melted at 210° C. is pulled at a take-up speed of 2.0 m / min. A device named "Capilograph" manufactured by Toyo Seiki Seisakusho Co., Ltd. can be used to measure the melt tension.

[0054] The component (B) is a crystalline thermoplastic resin mainly composed of structural units derived from propylene. Here, "mainly composed of structural units derived from propylene" means that, when the total mass of the component (B) is taken as 100 mass%, the structural units derived from propylene account for 80 mass% or more. The structural units derived from propylene account for 90 mass% or more.

[0055] Examples of the component (B) include a propylene homopolymer and a propylene random copolymer.

[0056] Examples of propylene random copolymers include: (1) A propylene-ethylene random copolymer containing a structural unit derived from propylene and a structural unit derived from ethylene. (2) A propylene-ethylene-α-olefin random copolymer containing a structural unit derived from propylene, a structural unit derived from ethylene, and a structural unit derived from an α-olefin having 4 to 20 carbon atoms. (3) A propylene-α-olefin random copolymer containing a structural unit derived from propylene and a structural unit derived from an α-olefin having 4 to 20 carbon atoms. etc.

[0057] Examples of methods for producing propylene homopolymers and propylene random copolymers include methods for polymerizing propylene and the like in the presence of known complex catalysts such as Ziegler-Natta catalysts, metallocene complexes, nonmetallocene complexes, etc. Examples of the polymerization methods include slurry polymerization, solution polymerization, bulk polymerization, and gas phase polymerization.

[0058] Among the above-listed examples of the component (B), it is preferable to use a propylene homopolymer, a copolymer of propylene and ethylene, or a copolymer of propylene, ethylene and 1-butene, and a propylene homopolymer is particularly preferable.

[0059] The maximum peak temperature measured by differential scanning calorimetry, i.e., the melting point (also referred to as "Tm" in this specification), of component (B) is preferably 100° C. or higher, and more preferably 120° C. or higher. When the melting point of component (B) is 100° C. or higher, sufficient melt tension and strength tend to be exhibited.

[0060] The density of the component (B) measured in accordance with JIS K7112 is not particularly limited, but is preferably 0.85 g / cm 3 More than 0.95g / cm 3 More preferably, it is 0.87 g / cm or less. 3 More than 0.93g / cm 3 The following is the result.

[0061] When the content of the (A) component in the thermoplastic resin composition according to this embodiment is 100 parts by mass, the content of the (B) component is preferably 1 to 2000 parts by mass, more preferably 5 to 1500 parts by mass, and particularly preferably 10 to 1000 parts by mass.

[0062] 1.3.(C) Component The thermoplastic resin composition according to the present embodiment contains a carbon-based filler (C). When the thermoplastic resin composition according to the present embodiment contains the component (C), the component (C) tends to be unevenly distributed in the continuous phase containing the component (A). This makes it possible to produce a molded article having better thermal conductivity and electrical conductivity than one in which the component (C) is uniformly dispersed in the resin composition. In addition, since the component (C) tends to be unevenly distributed in the continuous phase containing the component (A), interfacial peeling between the component (C) and the resin component is less likely to occur, and thus molding processability is improved. Furthermore, the specific gravity of the molded article obtained can be lowered by adding the component (C) compared to the case in which other fillers such as metal oxides are added.

[0063] Examples of the (C) component include natural graphite such as flake graphite, lump graphite, and earthy graphite; artificial graphite; carbon black such as furnace black, channel black, acetylene black, thermal black, and Ketjen black; carbon nanotubes such as single-walled carbon nanotubes and multi-walled carbon nanotubes; carbon fibers (carbon fibers) such as PAN-based and pitch-based; and graphene. Among these (C) components, natural graphite and carbon black are preferred from the viewpoint of thermal conductivity, flake graphite and acetylene black are more preferred, and acetylene black is particularly preferred from the viewpoint of cost and electrical conductivity. The (C) component may be used alone or in combination of two or more types.

[0064] The shape of component (C) is not particularly limited, and various shapes such as spherical, needle-like, fibrous, scale-like, dendritic, plate-like, and amorphous shapes can be mentioned, but it is preferable that the primary structure is either spherical, plate-like, or fibrous. Here, the "primary structure" refers to the structure of each component (C) before it forms an aggregate.

[0065] When the primary structure of the (C) component is spherical, plate-like, or fibrous, the average particle size in the case of spheres, the average thickness in the case of plates, or the average diameter in the case of fibers is preferably 1 μm or less, more preferably 1 to 500 nm, even more preferably 3 to 200 nm, and particularly preferably 5 to 100 nm. If the average particle size in the case of spheres, the average thickness in the case of plates, or the average diameter in the case of fibers of the (C) component are within the above ranges, the (C) component unevenly distributed in the continuous phase containing the (A) component is likely to form a heat conduction path or an electric conduction path, and a molded product with excellent thermal conductivity and electric conductivity is likely to be obtained. The average particle size in the case of spheres, the average thickness in the case of plates, or the average diameter in the case of fibers can be obtained as the average value of values ​​measured by observing 100 samples of the (C) component using a transmission electron microscope (TEM).

[0066] The volume fraction of the (C) component in the thermoplastic resin composition according to the present embodiment is preferably 15 to 40 volume%, more preferably 16 to 38 volume%, and particularly preferably 18 to 36 volume%. When the volume fraction of the (C) component is within the above range, the thermal conductivity and electrical conductivity of the resulting molded article can be ensured, and the content of the (C) component is relatively small, so that the flexibility is improved. In addition, the interfacial peeling between the (C) component and the resin component is less likely to occur, so that the moldability is improved.

[0067] When the content of the (A) component in the thermoplastic resin composition according to this embodiment is 100 parts by mass, the content of the (C) component is preferably 100 to 1000 parts by mass, more preferably 200 to 800 parts by mass, and particularly preferably 300 to 600 parts by mass.

[0068] 1.4. Other Additives In addition to the above-mentioned components, the thermoplastic resin composition according to the present embodiment may contain various additives as necessary, such as a foam nucleating agent, a lubricant, an antioxidant, a heat stabilizer, a weathering agent, and an extender oil.

[0069] 1.5. Characteristics of Thermoplastic Resin Composition It is presumed that the thermoplastic resin composition according to this embodiment forms a continuous phase containing the (A) component and a continuous or discontinuous phase containing the (B) component. The (C) carbon-based filler tends to be unevenly distributed in the continuous phase containing the (A) component. It is considered that the state in which the (C) component is unevenly distributed in the continuous phase containing the (A) component is more likely to form a heat conduction path or an electric conduction path by the (C) component than the state in which the (C) component is uniformly dispersed in the resin composition, and a molded product having excellent heat conductivity and electric conductivity is more likely to be obtained.

[0070] On the other hand, when the (C) component is highly filled, interfacial peeling occurs frequently at the interface between the (C) component and the resin component during molding, and the appearance of the molded product is easily damaged. However, in the thermoplastic resin composition according to this embodiment, the (C) component is unevenly distributed in the continuous phase containing the (A) component, so that a molded product having excellent thermal conductivity and electrical conductivity can be easily obtained even if the amount of the (C) component is reduced. Therefore, it is possible to reduce the amount of the (C) component, which in turn improves the moldability and the flexibility of the molded product.

[0071] Therefore, in the thermoplastic resin composition according to this embodiment, when the total mass of the component (C) is taken as 100 mass%, it is preferable that more than 50 mass%, preferably 60 mass% or more, more preferably 70 mass% or more, and particularly preferably 80 mass% or more of the component (C) is present in the continuous phase containing the component (A).

[0072] The thickness of the continuous phase containing the component (A) is preferably 5 μm or less, more preferably 4 μm or less, and particularly preferably 3 μm or less. The thickness of the continuous phase containing the component (A) is preferably 0.1 μm or more, more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. The "thickness of the continuous phase" is measured at the point where the width of the continuous phase sandwiched between the adjacent discontinuous phases is the widest, and can be calculated by averaging five measurements per sample.

[0073] 1.6. Method for producing thermoplastic resin composition The method for producing the thermoplastic resin composition according to the present embodiment is not particularly limited as long as it is a method that can sufficiently knead the (A) component, the (B) component, the (C) component, and other components. For example, a method of heating using a closed type kneader (roll mill, Labo Plasto Mill, Banbury mixer, pressure kneader, etc.), a single screw extruder, a twin screw extruder, or a continuous kneader, etc., and then kneading while applying an appropriate shear stress, can be mentioned. In addition, when kneading, each component may be kneaded at once, or a multi-stage division kneading method in which an arbitrary part of the components is kneaded and then the remaining components are added and kneaded can be adopted. For example, typical kneading conditions for Labo Plasto Mill are a kneading temperature of 150 to 250°C, a rotation speed of 40 to 80 rpm, and a kneading time of 5 to 60 minutes.

[0074] 1.7. Uses of thermoplastic resin compositions 1.7.1. Extrusions The thermoplastic resin composition according to the present embodiment can be extruded to produce an extrusion molded article. Examples of the extrusion molding method include melt extrusion and semi-melt extrusion, and the melt extrusion method is preferred. Examples of the melt extrusion method include methods using dies of various shapes, and among these, the method using a T-die or a coat hanger die is preferred.

[0075] In such melt extrusion, a heat-molten thermoplastic resin composition is extruded through a die, and then is brought into contact with a metal belt, a cooling roll, or the like to form a sheet. This polymer sheet is then cooled and wound up to obtain a roll-shaped polymer sheet.

[0076] This polymer sheet may be stretched before or after being wound into a roll, and may be cut to a predetermined size. The polymer sheet melt-extruded from the die may be blown with air controlled to the same temperature as the metal belt, or may be fixed by electrostatic charging, in order to adhere to the metal belt. The stretching may be uniaxial or biaxial.

[0077] 1.7.2. Foam mouldings A foamed molded article can be produced by foaming the thermoplastic resin composition according to this embodiment. In the obtained foamed molded article, the (C) component is unevenly distributed around the periphery of the formed bubbles (foam cells), and thus the (C) components come into close proximity or contact with each other by compression, forming a thermal conductive path or a conductive path, thereby improving the thermal conductivity and electrical conductivity. In addition, even if the blending amount of the (C) component is small, a foamed molded article having excellent thermal conductivity and electrical conductivity can be produced. In addition, since the blending amount of the (C) component can be reduced, the foamed molded article can be easily molded into any shape. The foamed molded article thus obtained can be used as a foam sheet used inside an electronic device.

[0078] When producing a foam molded article, a foam nucleating agent (nucleating agent) may be further added to the thermoplastic resin composition. Examples of foam nucleating agents include powders of inorganic compounds such as calcium carbonate, talc, mica, silica, and titania. By adding such a foam nucleating agent, the foam cell diameter can be easily adjusted, and a foam molded article having appropriate flexibility can be obtained. The particle size of the foam nucleating agent is not particularly limited, but is preferably 2 to 50 μm, more preferably 5 to 20 μm, from the viewpoint of keeping the diameter and number of the foam cells in an appropriate range and maintaining the cushioning properties of the foam molded article.

[0079] The content of the foaming nucleating agent is preferably 0 to 20 parts by mass, more preferably 0.01 to 15 parts by mass, and particularly preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the total mass of the resin components (in other words, the total amount of the components (A) and (B)). Note that the foaming nucleating agent is also preferably added to the component (A) as a master batch using, for example, the component (B).

[0080] 2. Working Example Specific examples of the present invention will be described below, but the present invention is not limited to these examples. In the following Production Examples, Examples, and Comparative Examples, "%" is based on mass unless otherwise specified.

[0081] 2.1. Production of hydrogenated butadiene block copolymers <Production Example 1> 24 kg of cyclohexane, 1 g of tetrahydrofuran, 1200 g of 1,3-butadiene, and 3.3 g of n-butyllithium were added to a nitrogen-purged reaction vessel having an internal volume of 50 L, and adiabatic polymerization was carried out from 70°C. After completion of the reaction, the temperature was lowered to 5°C, and 340 g of tetrahydrofuran and 2800 g of 1,3-butadiene were added to carry out adiabatic polymerization. After 30 minutes, 2.3 g of methyldichlorosilane was added, and the reaction was carried out for 15 minutes.

[0082] After the reaction was completed, hydrogen gas was supplied at a pressure of 0.4 MPa-G and the mixture was stirred for 20 minutes to react with the living anion at the polymer end lithium to produce lithium hydride. The reaction solution was heated to 90°C, 7.2 g of tetrachlorosilane was added, and the mixture was stirred for about 20 minutes. A hydrogenation catalyst mainly composed of a tanocene compound was added, and the hydrogenation reaction was carried out for 2 hours at a hydrogen pressure of 0.8 MPa. When hydrogen absorption was completed, the reaction solution was returned to room temperature and pressure and removed from the reaction vessel. The reaction solution was then stirred and poured into water, and the solvent was removed by steam distillation to obtain a hydrogenated block copolymer with an ABA structure, which is a hydrogenated diene polymer.

[0083] The hydrogenation rate of the obtained hydrogenated block copolymer was 99%, the number average molecular weight was 300,000, the 1,2-vinyl group content of the first stage polybutadiene block (A block) of the copolymer before hydrogenation was 15% (per one end), and the 1,2-vinyl group content of the second stage polybutadiene block (B block) of the copolymer before hydrogenation was 78%. The melt flow rate of the hydrogenated block copolymer measured at 230°C and 21.2N was 2.5g / 10min.

[0084] <Production Example 2> In a 3-liter stirring vessel, 100 g of EP57C (ethylene-propylene rubber) manufactured by JSR Corporation was dissolved in 1 kg of cyclohexane, and then 1 kg of LUCANT LX020, a liquid ethylene-α-olefin copolymer manufactured by Mitsui Chemicals, was added and stirred until the mixture became homogeneous. After stirring was completed, the resulting solution was concentrated in an evaporator to remove the cyclohexane, synthesizing an ethylene-α-olefin copolymer containing a liquid polymer that does not have a melting point of 23°C or higher due to the ethylene crystal structure.

[0085] 2.2. Preparation of thermoplastic resin composition The types and amounts of ethylene-α-olefin copolymer (X), polypropylene thermoplastic resin (Y), filler, and olefin wax (product name "Sunwax 161-P", manufactured by Sanyo Chemical Industries, Ltd.) shown in Table 1 or Table 2 below were added to a 100 cc Labo Plastomill, and 150 parts by mass of extender oil (product name "Diana Process Oil PW-380", manufactured by Idemitsu Kosan Co., Ltd.), 14 parts by mass of fatty acid amide (product name "Neutron S", manufactured by Nippon Fine Chemical Industries Co., Ltd.), and 1 part by mass of antioxidant (product name "Irganox 1010", manufactured by BASF Japan) were further added and melt-kneaded under conditions of set temperature of 180°C, 60 rpm, and 10 min. to produce each thermoplastic resin composition used in Examples 1 to 14 and Comparative Examples 1 to 4.

[0086] Each thermoplastic resin composition thus obtained was observed using a transmission electron microscope (TEM) (Hitachi High-Tech Corporation, model number "HITACHI H-7650") to confirm the dispersion state of the filler and the thickness of the ethylene-α-olefin copolymer (X) phase. The thickness of the ethylene-α-olefin copolymer (X) phase was calculated as the average value of the values ​​measured for 100 samples. The results are also shown in Tables 1 and 2 below. FIG. 1 shows a TEM photograph showing the continuous phase structure containing the ethylene-α-olefin copolymer (X) of the thermoplastic resin composition produced in Example 8. FIG. 2 shows a TEM photograph of an enlarged portion of FIG. 1. FIG. 3 shows a TEM photograph showing the continuous phase structure containing the ethylene-α-olefin copolymer (X) of the thermoplastic resin composition produced in Comparative Example 4.

[0087] 2.3.Preparation of the sheet The thermoplastic resin composition obtained above was fed to a twin-screw extruder "KTX30" (model name) manufactured by Kobe Steel, Ltd., and melt-kneaded under conditions of a cylinder temperature of 210°C, a screw rotation speed of 300 rpm, and a discharge rate of 30 kg / h to obtain cylindrical pellets with a diameter of 2 mm and a length of 4 mm. The produced pellets were press-molded by an electric heat press using a sheet mold of 120 mm x 120 mm x 2 mm (length x width x thickness) at 190°C and a pressure of 15 MPa to produce sheet-shaped test pieces.

[0088] 2.4.Evaluation Methodology <Evaluation of thermal conductivity> The sheet prepared above was further pressed at 190°C and 5 MPa to obtain 3 A test plate with a thickness of 100 μm was obtained. The thermal conductivity [W / m K] of the obtained test plate was calculated using a thermal resistance measuring device conforming to ASTM D5470. The evaluation criteria are as follows. (Evaluation Criteria) A: Thermal conductivity is 0.8 W / m K or more. B: Thermal conductivity is 0.5 W / m K or more and less than 0.8 W / m K. C: Thermal conductivity is less than 0.5 W / m K.

[0089] <Gross evaluation> The 2 mm thick sheets thus produced were punched out into 1.5 cm squares, and the specific gravity was calculated using the water displacement method in accordance with ISO 1183. The evaluation criteria were as follows: (Evaluation Criteria) A: The specific gravity is less than 1.3. B: Specific gravity is 1.3 or more and less than 1.5. C: Specific gravity is 1.5 or more.

[0090] <Evaluation of volume resistivity> The volume resistivity of the center and four corners of the 2 mm thick sheet was measured by the four-point probe method using an electrical resistance measuring device conforming to ISO 3915, and the average value was taken as the volume resistivity [Ω] of the sample. The evaluation criteria are as follows: (Evaluation Criteria) A: Volume resistivity is 1.0×10 2 It is less than Ω. B: Volume resistivity is 1.0×10 2 Ω or more 1.0×10 6 It is less than Ω. C: Volume resistivity is 1.0×10 6 More than Ω.

[0091] <Evaluation of flexibility (bendability)> The 2 mm thick sheet was folded back and forth at an angle of 150°, and the sample was observed for cracks. The same operation was repeated 30 times, and the flexibility of the sample was evaluated based on the number of times the sample cracked. The evaluation criteria were as follows: (Evaluation Criteria) A: Cracks occurred after 21 or more times, or no cracks occurred after 30 times. B: Cracks appeared after 10 to 20 times. C: Cracks occurred after 1 to 9 tries.

[0092] <Evaluation of extrusion processability> The produced sheet was cut into small pieces and fed into a 100cc Labo Plastomill, and extruded at 220°C using a 2mm thick flat die to produce an extruded ribbon. The resulting ribbon was visually inspected for edge cuts, burrs, undulations, and the presence or absence of bumps, and rated on a 5-point scale. The evaluation criteria are as follows: (Evaluation Criteria) 5: The appearance is excellent and free of defects. 4: Appearance is good with few defects. 3: Few defects in appearance and no problems in use. 2: Some defects in appearance are observed, but they do not affect use. 1: Numerous defects in appearance are found and the item cannot be used.

[0093] 2.5.Evaluation Results Tables 1 and 2 below show the compositions of the thermoplastic resin compositions prepared in the examples and comparative examples, as well as the evaluation results.

[0094] [Table 1]

[0095] [Table 2]

[0096] The components shown in Tables 1 and 2 above were used as follows. <Ethylene-α-olefin copolymer (X)> Hydrogenated butadiene block copolymer: Synthesized in Production Example 1 above, Durometer hardness: 66A, Melting point: 95°C Ethylene-(ethylene-octene) block copolymer: Product name "INFUSE9100", manufactured by Dow Chemical Japan Co., Ltd., Durometer hardness: 75A, Melting point: 120℃ Ethylene-octene random copolymer: Product name "ENGAGE8100", manufactured by Dow Chemical Japan Co., Ltd., Durometer hardness: 73A, Melting point: 60℃ LLDPE: Product name "UF420", manufactured by Japan Polyethylene Co., Ltd., durometer hardness >90A, melting point: 123℃ EPDM-1: Product name "EP57C", manufactured by JSR Corporation, no melting point, no liquid polymer EPDM-2: Synthesized in Production Example 2 above, no melting point, contains liquid polymer The durometer hardness was measured using a type A durometer conforming to JIS K 6253. The melting point was determined as the temperature at which the heat absorption due to crystal melting peaked in a melting curve obtained using a differential scanning calorimeter (DSC). <Polypropylene-based thermoplastic resin (Y)> Long-chain branched PP: Product name "Novatec PP EA9HD", manufactured by Japan Polypropylene Corporation, melt tension at 210°C: 20cN Linear PP: Product name "Novatec PP FA3EC", manufactured by Japan Polypropylene Corporation, melt tension at 210°C: 1cN The melt tension was measured using a "Capilograph" device manufactured by Toyo Seiki Seisakusho, Ltd., by measuring the tension generated when a polypropylene-based thermoplastic resin (Y) heated and melted at 210°C was pulled at a take-up speed of 2.0 m / min. <Filler> Flake zinc: Product name "Z-5F", Ito Graphite Industries Co., Ltd., average particle size: 4 μm, specific gravity: 2.1 Acetylene black: Product name "Denka Black Granules", manufactured by Denka Co., Ltd., primary particle size: 43 nm, specific gravity: 1.9 Ketjen Black: Product name "EC600JD", manufactured by Lion Specialty Chemicals Co., Ltd., Primary particle size: 34 nm, Specific gravity: 1.8 Graphene: Product name "N006-PR", manufactured by Angstron Materials, thickness of primary structure: 20 nm, specific gravity: 2.1 Carbon nanotubes: Product name "NC7000", manufactured by Nanocyl SA, primary structure diameter: 9.5 nm, specific gravity: 2.1 Alumina: Product name "DAM-05", manufactured by Denka Co., Ltd., average particle size: 5 μm, specific gravity: 3.9 <Other ingredients> Extension oil: Product name "Diana Process Oil PW-380", manufactured by Idemitsu Kosan Co., Ltd. Olefin wax: Product name "Sanwax 161-P", manufactured by Sanyo Chemical Industries, Ltd., low molecular weight polyethylene, weight average molecular weight: 30,000 Fatty acid amide: Trade name "Neutron S", manufactured by Nippon Fine Chemical Co., Ltd., erucic acid amide Antioxidant: Product name "Irganox 1010", manufactured by BASF Japan Ltd., a hindered phenol-based antioxidant

[0097] From the evaluation results in Tables 1 and 2 above, it was confirmed that in the thermoplastic resin compositions of Examples 1 to 14, the carbon-based filler was unevenly distributed in the ethylene-α-olefin copolymer (X). FIG. 1 is a TEM photograph showing a continuous phase structure containing the ethylene-α-olefin copolymer (X) of the thermoplastic resin composition produced in Example 8, and FIG. 2 is a TEM photograph showing an enlarged portion of FIG. 1. In FIGS. 1 and 2, the dark colored areas are the phase of the ethylene-α-olefin copolymer (X) in which the carbon-based filler is unevenly distributed. As a result, heat conductive paths and electric conductive paths are easily formed in the molded body, and a molded body with excellent heat conductivity and electric conductivity can be obtained. It was also found that the molded articles made from the thermoplastic resin compositions of Examples 1 to 14 were excellent in flexibility. Furthermore, the thermoplastic resin compositions of Examples 1 to 14 also had good extrusion processability.

[0098] The thermoplastic resin composition of Comparative Example 1 uses LLDPE having a durometer hardness exceeding 90A instead of component (A). Although the carbon-based filler is unevenly distributed in the continuous phase of the LLDPE, this LLDPE is too hard, making it difficult to form a heat conductive path or an electric conductive path within the molded body, and a molded body having poor thermal conductivity and electric conductivity was obtained. In addition, it was found that the molded body made from the thermoplastic resin composition of Comparative Example 1 also had poor flexibility. Furthermore, the thermoplastic resin composition of Comparative Example 1 also had poor extrusion processability.

[0099] The thermoplastic resin composition of Comparative Example 2 uses alumina instead of component (C). Since alumina is dispersed without being unevenly distributed in the continuous phase of the ethylene-α-olefin copolymer (X), a molded article having poor thermal conductivity and electrical conductivity was obtained. In addition, it was found that the molded article made from the thermoplastic resin composition of Comparative Example 2 also had poor flexibility due to the inclusion of alumina. Furthermore, the extrusion molded article made from the thermoplastic resin composition of Comparative Example 2 had many defects in appearance and was also poor in extrusion processability.

[0100] The thermoplastic resin composition of Comparative Example 3 uses linear PP having a low melt tension instead of component (B). This thermoplastic resin composition has a low melt tension, and therefore has poor extrusion processability. In addition, it was found that the molded article made from the thermoplastic resin composition of Comparative Example 3 is not excellent in flexibility, thermal conductivity, or electrical conductivity.

[0101] The thermoplastic resin composition of Comparative Example 4 uses EPDM-2, which has no melting point, instead of component (A). Since the compatibility between EPDM-2 containing a carbon-based filler and component (B) is not very good, it becomes difficult to form a heat conductive path or an electric conductive path in the molded body, and a molded body with poor thermal conductivity and electric conductivity is obtained. In addition, it was found that the molded body made from the thermoplastic resin composition of Comparative Example 4 is also poor in flexibility. Furthermore, the thermoplastic resin composition of Comparative Example 4 also had poor extrusion processability.

[0102] The present invention is not limited to the above-described embodiments, and various modifications are possible. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above-described embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above-described embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above-described embodiments.

Claims

1. (A) a polymer having a durometer hardness of 90A or less and a melting point of 23°C or more; (B) a polypropylene-based thermoplastic resin having a melt tension of 3.0 cN or more at 210° C. and a take-up speed of 2.0 m / min; and (C) Carbon-based filler containing natural graphite or carbon black A thermoplastic resin composition comprising: The (A) polymer has a melting point of 23° C. or higher derived from an ethylene crystal structure, A thermoplastic resin composition, characterized in that the content of the component (C) is 200 to 800 parts by mass when the content of the component (A) is 100 parts by mass.

2. The thermoplastic resin composition according to claim 1, wherein the polymer (A) has a melting enthalpy of 5 to 150 J / g as measured by a differential scanning calorimeter under the following conditions: conditions: (1) Cool from 200°C to -150°C at 10°C / min (2) Hold at -150°C for 1 minute (3) Heat from -150°C to 200°C at 20°C / min.

3. The thermoplastic resin composition according to claim 1 or 2, wherein the polymer (A) comprises one or more polymers selected from hydrogenated diene polymers and ethylene-α-olefin polymers.

4. The hydrogenated diene polymer is It is obtained by hydrogenating a conjugated diene triblock copolymer having blocks A at both ends and block B in the middle, the block A has a 1,2-vinyl group content of less than 25 mol % and the block B has a 1,2-vinyl group content of 25 mol % or more; When the entire conjugated diene triblock copolymer is taken as 100% by mass, the block A is 5 to 90% by mass and the block B is 10 to 95% by mass, The bifunctional monomer derived from the conjugated diene monomer unit contained in the conjugated diene triblock copolymer More than 80% of the heavy bonds are hydrogenated, The thermoplastic resin composition according to claim 3, having a number average molecular weight after hydrogenation of 50,000 to 700,000.

5. The primary structure of the (C) carbon-based filler is either spherical or plate-shaped, 5. The thermoplastic resin composition according to claim 1, wherein the average particle diameter in the case of a sphere and the average thickness in the case of a plate are 1 μm or less.

6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein the volume fraction of the (C) carbon-based filler in the thermoplastic resin composition is 15 to 40 volume %.

7. The polymer (A) and the thermoplastic resin (B) form a continuous phase containing the polymer (A) and a continuous or discontinuous phase containing the thermoplastic resin (B); The thermoplastic resin composition according to claim 1 , wherein more than 50 mass% of the (C) carbon-based filler is present in the continuous phase containing the (A) polymer.

8. The thermoplastic resin composition according to claim 7, wherein the thickness of the continuous phase containing the polymer (A) is 5 μm or less.

9. An extrusion molded article produced using the thermoplastic resin composition according to any one of claims 1 to 8.

10. A foamed molded article produced using the thermoplastic resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Vinyl chloride-based resin and its production

    JP1998251354A

  • Urethane elastomer composition

    JP2001234056A

  • Foamed molded body of polypropylene resin

    JP2002018887A

  • Thermoplastic elastomer composition and molded foam article

    JP2013159753A

  • Polyolefin-based resin thin layer foamed sheet and its manufacturing method, its use

    JP2014062245A